Some endpoint inequalities for multilinear integral operators - Liu, L. (Український математичний вісник, 2006)
In this paper, the endpoint estimates for some multilinear operators related to certain fractional singular integral operators are obtained. The operators include Calder´on–Zygmund singular integral operator and fractional integral operator.